THE ROLE OF THE STATE IN ISLAMIC FINANCE DEVELOPMENT: A WORLDWIDE GOVERNANCE INDICATOR APPROACH - Sakifah Ismail; Nuhbatul Basyariah (IQTISHADUNA, 2022)
This research aims to empirically examine the institutional quality variable as a moderatingvariable between macroeconomic stability and the development of global Islamic finance andthe indicators of global sukuk instruments. This is to prove previous research which states thatmacroeconomic stability influences financial developments. Macroeconomic stability alsoinfluences the development of the sukuk market. There is empirical research that states thatinstitutional quality moderate financial developments, so research is directed at examininginstitutional quality as a moderator of macroeconomic stability in the development of the globalsukuk market. Exploratory quantitative research method, using secondary data panel datamodels in the form of development of sukuk with proxies for issuance of sukuk in countriesthat are active in issuing sukuk and registered on the International Islamic Financial Market(IIFM), and institutional quality comes from WGI -BI. The results of the analysis show that thequality of institutions moderates the macroeconomic stability of the development of sukuk,especially on the exchange rate and inflation indicators. While the GDPP moderation test forthe development of sukuk there is no evidence that institutional quality is a moderating variable.This research contributes empirically to the limitations of previous research which analyzedmacroeconomic stability without including the variable quality of government institutionswhich can be used as a basis for making decisions for investors in investing, regulators in makingrules, and issuers when issuing sukuk.